Pills, Power, and Policy : The Struggle for Drug Reform in Cold War America and Its Consequences - Tobbell, Dominique A., 1978- (Book collections on Project MUSE., 2012)
Since the 1950s, the American pharmaceutical industry has been heavily criticized for its profit levels, the high cost of prescription drugs, drug safety problems, and more, yet it has, together with the medical profession, staunchly and successfully opposed regulation. Pills, Power, and Policyoffers a lucid history of how the American drug industry and key sectors of the medical profession came to be allies against pharmaceutical reform. It details the political strategies they have used to influence public opinion, shape legislative reform, and define the regulatory environment of prescriptio.